From Bandung with love / Mahizan Hijaz Mohammad - Hijaz Mohammad, Mahizan (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
On April 27, 2019, Faculty of Art and Design (FSSR), UiTM Perak Branch received an academic visit by the delegation from Institute Seni Budaya Indonesia Bandung (ISBI). The delegation consisted of representatives from ISBI who were led by Dr. Dede.